# Solve for z -8(4+9z)=7(-2-11z) -8(4+9z)=7(-2-11z)
Simplify -8(4+9z).
Apply the distributive property.
-8⋅4-8(9z)=7(-2-11z)
Multiply.
Multiply -8 by 4.
-32-8(9z)=7(-2-11z)
Multiply 9 by -8.
-32-72z=7(-2-11z)
-32-72z=7(-2-11z)
-32-72z=7(-2-11z)
Simplify 7(-2-11z).
Apply the distributive property.
-32-72z=7⋅-2+7(-11z)
Multiply.
Multiply 7 by -2.
-32-72z=-14+7(-11z)
Multiply -11 by 7.
-32-72z=-14-77z
-32-72z=-14-77z
-32-72z=-14-77z
Move all terms containing z to the left side of the equation.
Add 77z to both sides of the equation.
-32-72z+77z=-14
Add -72z and 77z.
-32+5z=-14
-32+5z=-14
Move all terms not containing z to the right side of the equation.
Add 32 to both sides of the equation.
5z=-14+32
Add -14 and 32.
5z=18
5z=18
Divide each term by 5 and simplify.
Divide each term in 5z=18 by 5.
5z5=185
Cancel the common factor of 5.
Cancel the common factor.
5z5=185
Divide z by 1.
z=185
z=185
z=185
The result can be shown in multiple forms.
Exact Form:
z=185
Decimal Form:
z=3.6
Mixed Number Form:
z=335
Solve for z -8(4+9z)=7(-2-11z)

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top